Preparation method for obtaining lightweight high-toughness beryllium-aluminum composite material with strong interface bonding through matrix alloying

By introducing Zn and V alloy elements into beryllium aluminum composite material and combining the regulation interface, the problem of the beryllium aluminum interface is solved, and the lightweight and high strength properties of the material are achieved.

CN119491130APending Publication Date: 2025-02-21HARBIN INST OF TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411683704.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the preparation of beryllium aluminum composite materials, the interface of beryllium aluminum is not easy to regulate, resulting in limited material mechanical properties.

Method used

Through the design of matrix alloy components, the regulation of interface combination is used to introduce Zn and V alloy elements to generate reinforced phases and eutectics, and the interface combination method is improved, thereby achieving strong interface combination.

Benefits of technology

It effectively improves the strength, stiffness and ductility of beryllium aluminum composite material, solves the problem of low interface bonding strength, and achieves lightweight, high-strength material properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491130A_ABST
    Figure CN119491130A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a lightweight high-toughness beryllium-aluminum composite material, in particular to a preparation method of a lightweight high-toughness beryllium-aluminum composite material capable of obtaining strong interface bonding through matrix alloying. In order to solve the problem that the mechanical property of the material is limited due to the fact that a beryllium-aluminum interface is not easy to regulate and control in the preparation of the beryllium-aluminum composite material, the invention provides a preparation method for obtaining the lightweight and high-toughness beryllium-aluminum composite material with strong interface combination through matrix alloy component design and interface combination regulation and control. The added Zn element can react with a BeO layer on the surface of the beryllium powder to generate a ZnxBe (1-x) O interface strengthening phase at a Be-Al interface, a stable oxide layer on the surface of the beryllium powder is destroyed, immersion of molten aluminum is facilitated, BeAl2O4 can be formed to realize connection of the beryllium-aluminum interface, and the surface of the beryllium powder is protected. An interface bonding mode is converted from an initial beryllium-aluminum direct bonding type interface to a reaction type interface bonding of strong interface bonding; and the V element can improve the brittleness of beryllium and improve the ductility of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a lightweight high-strength and toughness beryllium aluminum composite material. Background Art

[0002] With the continuous development of the times, the aerospace and other fields have put forward requirements for light weight, high strength and high stiffness of materials. Aluminum and aluminum alloys can only meet the requirements of light weight, while aluminum-based composites have higher strength and stiffness than the matrix aluminum alloy, and have attracted much attention from researchers. Among many aluminum-based composite materials, beryllium aluminum composites have a lower density than aluminum (2.7g / cm 3 ), machinability, higher specific stiffness, and higher specific strength have attracted much attention from researchers. At present, the AlBeMet162 (AM162 for short) blank developed by Materion Company in the United States has a density of 2.1g / cm 3 , the elastic modulus can reach 193GPa, the tensile strength is 262MPa, and it is widely used in the aerospace field, such as F-35 fighter jets, electronic devices, and satellites.

[0003] From the phase diagram of beryllium-aluminum binary alloy, it can be seen that the melting point difference between beryllium and aluminum is large, there is no intermediate product, and the wettability between beryllium and aluminum is low. These factors lead to the beryllium-aluminum interface being a direct bonding interface with low interface bonding strength, which makes it difficult to improve the mechanical properties of the material. Currently, the commonly used methods for preparing beryllium-aluminum alloys are casting and powder metallurgy. In the casting method, beryllium powder is melted and mixed with aluminum and the corresponding alloying elements are added. However, due to the large difference in melting points between beryllium and aluminum, which is 1287°C and 660°C, coarse beryllium dendrites and other casting defects will be generated during solidification, affecting the performance of the material. The powder metallurgy method is to press aluminum powder and beryllium powder into shape and then sinter them to prepare the corresponding composite material. Due to process reasons, pure beryllium, pure aluminum powder or beryllium aluminum pre-alloyed powder formed by the two is mostly used without the introduction of alloying elements. Summary of the invention

[0004] In order to solve the problem that the beryllium aluminum interface is difficult to control in the preparation of beryllium aluminum composite materials, resulting in limited mechanical properties of the material, the present invention provides a preparation method for a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding, which can be obtained by designing the matrix alloy composition and controlling the interface bonding.

[0005] The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding by matrix alloying of the present invention is carried out in the following steps:

[0006] 1. Weighing of raw materials:

[0007] Weigh beryllium powder in a sealed glove box; weigh Al-Zn master alloy block, Al-V master alloy block and pure aluminum block at the same time;

[0008] The ratio of the mass of the beryllium powder to the total mass of the Al-Zn master alloy block, the Al-V master alloy block and the pure aluminum block is 1:10-20;

[0009] 2. Preparation of Beryllium Powder Preform

[0010] The beryllium powder weighed in step 1 is placed in a mold, compacted, and then cold pressed to obtain a preform;

[0011] 3. Preparation of Beryllium Aluminum Composite Materials

[0012] The Al-Zn master alloy block, the Al-V master alloy block and the pure aluminum block weighed in step 1 are melted to obtain a liquid alloy, the liquid alloy is poured into a mold containing a preform, the mold is preheated and pressure infiltration is performed, and a beryllium / aluminum composite material is obtained after solidification;

[0013] The mechanical pressure applied during the pressure infiltration is 80-120 MPa, and the pressure holding time is 1-5 min;

[0014] 4. Heat treatment of beryllium aluminum composite materials

[0015] The beryllium / aluminum composite material obtained in step three is annealed.

[0016] Principle and beneficial effects of the present invention:

[0017] 1. The present invention prepares metal beryllium powder into a preform, and then pours molten liquid alloy into a mold containing the beryllium powder preform, and introduces alloy elements through the combination of solid beryllium powder and liquid aluminum; it can avoid coarse dendrites generated in the casting method due to the large difference in melting points of beryllium and aluminum and the high melting latent heat of beryllium powder, and solves the problem of difficulty in adding alloy elements in the powder metallurgy method, and the diffusion ability of alloy elements from aluminum liquid to solid beryllium powder is higher than the diffusion ability of solid aluminum powder to solid beryllium powder.

[0018] 2. The present invention introduces Zn and V alloy elements, wherein the added Zn element can react with the BeO layer on the surface of the beryllium powder to generate Zn at the Be-Al interface. x Be 1-x O interface strengthening phase destroys the stable oxide layer on the surface of beryllium powder, which is beneficial to the infiltration of aluminum liquid. BeAl2O4 can be formed to connect the beryllium-aluminum interface, and the interface bonding mode is transformed from the initial beryllium-aluminum direct bonding interface to a strong interface bonding reaction interface bonding. In addition, the Zn element has a high solid solubility in aluminum and is mainly distributed in the aluminum matrix, which can also improve the matrix strength.

[0019] 3. When the BeO layer of the beryllium powder is destroyed, the V element introduced in the present invention can smoothly break through the BeO layer and contact the Be element, diffuse into the beryllium particles, and wrap the beryllium powder (hard area) through the eutectic (soft area) generated by Be and V to form a soft-hard combination area structure, which can improve the brittleness of beryllium and the ductility of the material, and achieve the strengthening and toughening of the beryllium aluminum composite material together with the Zn element.

[0020] 4. The present invention performs high-temperature annealing treatment on the extruded beryllium / aluminum composite material to promote the diffusion of Zn and V elements in the composite material. The shorter insulation time can retain the strengthening phase in the material and maintain the strength of the matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The SEM and element distribution diagram of the beryllium aluminum composite material obtained in Example 2. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0023] Specific implementation method 1: In this implementation method, a method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding by matrix alloying is carried out in the following steps:

[0024] 1. Weighing of raw materials:

[0025] Weigh beryllium powder in a sealed glove box; weigh Al-Zn master alloy block, Al-V master alloy block and pure aluminum block at the same time;

[0026] The ratio of the mass of the beryllium powder to the total mass of the Al-Zn master alloy block, the Al-V master alloy block and the pure aluminum block is 1:10-20;

[0027] 2. Preparation of Beryllium Powder Preform

[0028] The beryllium powder weighed in step 1 is placed in a mold, compacted, and then cold pressed to obtain a preform;

[0029] 3. Preparation of Beryllium Aluminum Composite Materials

[0030] The Al-Zn master alloy block, the Al-V master alloy block and the pure aluminum block weighed in step 1 are melted to obtain a liquid alloy, the liquid alloy is poured into a mold containing a preform, the mold is preheated and pressure infiltration is performed, and a beryllium / aluminum composite material is obtained after solidification;

[0031] The mechanical pressure applied during the pressure infiltration is 80-120 MPa, and the pressure holding time is 1-5 min;

[0032] 4. Heat treatment of beryllium aluminum composite materials

[0033] The beryllium / aluminum composite material obtained in step three is annealed.

[0034] This embodiment has the following beneficial effects:

[0035] 1. In this embodiment, metal beryllium powder is prepared into a preform, and then the molten liquid alloy is poured into a mold containing the beryllium powder preform, and the alloy elements are introduced by combining the solid beryllium powder with the liquid aluminum. This can avoid the coarse dendrites produced in the casting method due to the large difference in melting points between beryllium and aluminum and the high melting latent heat of beryllium powder, and solves the problem of difficulty in adding alloy elements in the powder metallurgy method. In addition, the diffusion ability of the alloy elements from the aluminum liquid to the solid beryllium powder is higher than the diffusion ability of the solid aluminum powder to the solid beryllium powder.

[0036] 2. This embodiment introduces Zn and V alloy elements, wherein the added Zn element can react with the BeO layer on the surface of the beryllium powder to generate Zn at the Be-Al interface. x Be 1-x O interface strengthening phase destroys the stable oxide layer on the surface of beryllium powder, which is beneficial to the infiltration of aluminum liquid. BeAl2O4 can be formed to connect the beryllium-aluminum interface, and the interface bonding mode is transformed from the initial beryllium-aluminum direct bonding interface to a strong interface bonding reaction interface bonding. In addition, the Zn element has a high solid solubility in aluminum and is mainly distributed in the aluminum matrix, which can also improve the matrix strength.

[0037] 3. When the BeO layer of the beryllium powder is destroyed, the V element introduced in this embodiment can successfully break through the BeO layer and contact the Be element, diffuse into the beryllium particles, and wrap the beryllium powder (hard area) through the eutectic (soft area) generated by Be and V to form a soft-hard combination area structure, which can improve the brittleness of beryllium and improve the ductility of the material, and together with the Zn element, realize the strengthening and toughening of the beryllium aluminum composite material.

[0038] 4. In this embodiment, the extruded beryllium / aluminum composite material is subjected to high-temperature annealing treatment to promote the diffusion of Zn and V elements in the composite material. A shorter insulation time can retain the strengthening phase in the material and maintain the strength of the matrix.

[0039] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the purity of the beryllium powder in step 1 is 99%.

[0040] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the purity of the pure aluminum block in step one is 99.99%.

[0041] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the beryllium powder particles in the beryllium powder in step 1 are spherical or strip-shaped.

[0042] Specific implementation method five: This implementation method is different from any one of specific implementation methods one to four in that: the cold pressing pressure in step two is 50 MPa, and the pressure holding time is 10 to 15 minutes.

[0043] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that the smelting temperature in step 3 is 800-860°C.

[0044] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 1 to 6 in that: the smelting temperature in step 3 is 850°C.

[0045] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the temperature of the mold preheating in step three is 250°C to 350°C.

[0046] Specific implementation method 9: This implementation method is different from any one of specific implementation methods 1 to 8 in that: the temperature of the mold preheating in step 3 is 300°C.

[0047] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that: the annealing process described in step four is: the temperature is 420° C. to 520° C., and the insulation time is 0.5 h to 2 h.

[0048] Embodiment 1:

[0049] The preparation method of the lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying in this embodiment is carried out in the following steps:

[0050] 1. Weighing of raw materials:

[0051] 50g of beryllium powder was weighed in a sealed glove box; 100g of Al-Zn10 master alloy block, 200g of Al-V5 master alloy block and 700g of pure aluminum block were weighed at the same time; the purity of the beryllium powder was 99%; the purity of the pure aluminum block was 99.99%; the mass fraction of Zn in Al-Zn10 was 10%; the mass fraction of V in Al-V5 was 5%;

[0052] The beryllium powder particles in the beryllium powder are spherical;

[0053] 2. Preparation of Beryllium Powder Preform

[0054] The beryllium powder weighed in step 1 is placed in a mold, compacted, and then cold pressed to obtain a preform;

[0055] The cold pressing pressure is 50 MPa, and the pressure holding time is 15 min; the inner diameter of the cold pressing mold used is 35 mm;

[0056] 3. Preparation of Beryllium Aluminum Composite Materials

[0057] The Al-Zn10 master alloy block, the Al-V5 master alloy block and the pure aluminum block weighed in step 1 are melted to obtain a liquid alloy, the liquid alloy is poured into a mold containing a preform, the mold is preheated and pressure infiltration is performed, and a beryllium / aluminum composite material is obtained after solidification;

[0058] The smelting temperature is 850°C;

[0059] The mechanical pressure applied during the pressure infiltration is 100 MPa, and the holding time is 3 min;

[0060] The mold preheating temperature is 300°C;

[0061] 4. Heat treatment of beryllium aluminum composite materials

[0062] Annealing the beryllium / aluminum composite material obtained in step 3;

[0063] The annealing process is as follows: the temperature is 470°C and the holding time is 1.5h;

[0064] The density of the beryllium aluminum composite material obtained in Example 1 is 99%. After testing, the elastic modulus of the beryllium aluminum composite material is 200 GPa, the tensile strength is 500 MPa, and the elongation is 5.2%.

[0065] Embodiment 2:

[0066] The preparation method of the lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying in this embodiment is carried out in the following steps:

[0067] 1. Weighing of raw materials:

[0068] 50g of beryllium powder was weighed in a sealed glove box; 100g of Al-Zn10 master alloy block, 400g of Al-V5 master alloy block and 500g of pure aluminum block were weighed at the same time; the purity of the beryllium powder was 99%; the purity of the pure aluminum block was 99.99%; the mass fraction of Zn in Al-Zn10 was 10%; the mass fraction of V in Al-V5 was 5%;

[0069] The beryllium powder particles in the beryllium powder are spherical;

[0070] 2. Preparation of Beryllium Powder Preform

[0071] The beryllium powder weighed in step 1 is placed in a mold, compacted, and then cold pressed to obtain a preform;

[0072] The cold pressing pressure is 50 MPa, and the pressure holding time is 15 min; the inner diameter of the cold pressing mold used is 35 mm;

[0073] 3. Preparation of Beryllium Aluminum Composite Materials

[0074] The Al-Zn10 master alloy block, the Al-V5 master alloy block and the pure aluminum block weighed in step 1 are melted to obtain a liquid alloy, the liquid alloy is poured into a mold containing a preform, the mold is preheated and pressure infiltration is performed, and a beryllium / aluminum composite material is obtained after solidification;

[0075] The smelting temperature is 850°C;

[0076] The mechanical pressure applied during the pressure infiltration is 100 MPa, and the holding time is 3 min;

[0077] The mold preheating temperature is 300°C;

[0078] 4. Heat treatment of beryllium aluminum composite materials

[0079] Annealing the beryllium / aluminum composite material obtained in step 3;

[0080] The annealing process is as follows: the temperature is 470° C. and the holding time is 1.5 h.

[0081] Figure 1 The SEM and element distribution diagram of the beryllium aluminum composite material obtained in Example 2 shows that the O element is mainly distributed at the interface between the beryllium particles and the aluminum matrix, the distribution area of ​​the Zn element overlaps with the O element, and the V element can diffuse into the beryllium particles and distribute at the beryllium-aluminum interface, and the Zn element is distributed in the aluminum matrix, which can improve the matrix strength, indicating that the added alloy elements are effective. The density of the beryllium aluminum composite material obtained in Example 2 is 99%, the elastic modulus is 202GPa, the tensile strength is 600MPa, and the elongation is 6.5%.

[0082] Embodiment 3:

[0083] The preparation method of the lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying in this embodiment is carried out in the following steps:

[0084] 1. Weighing of raw materials:

[0085] 50g of beryllium powder was weighed in a sealed glove box; 200g of Al-Zn10 master alloy block, 200g of Al-V5 master alloy block and 600g of pure aluminum block were weighed at the same time; the purity of the beryllium powder was 99%; the purity of the pure aluminum block was 99.99%; the mass fraction of Zn in Al-Zn10 was 10%; the mass fraction of V in Al-V5 was 5%;

[0086] The beryllium powder particles in the beryllium powder are spherical;

[0087] 2. Preparation of Beryllium Powder Preform

[0088] The beryllium powder weighed in step 1 is placed in a mold, compacted, and then cold pressed to obtain a preform;

[0089] The cold pressing pressure is 50 MPa, and the pressure holding time is 15 min; the inner diameter of the cold pressing mold used is 35 mm;

[0090] 3. Preparation of Beryllium Aluminum Composite Materials

[0091] The Al-Zn10 master alloy block, the Al-V5 master alloy block and the pure aluminum block weighed in step 1 are melted to obtain a liquid alloy, the liquid alloy is poured into a mold containing a preform, the mold is preheated and pressure infiltration is performed, and a beryllium / aluminum composite material is obtained after solidification;

[0092] The smelting temperature is 850°C;

[0093] The mechanical pressure applied during the pressure infiltration is 100 MPa, and the holding time is 3 min;

[0094] The mold preheating temperature is 300°C;

[0095] 4. Heat treatment of beryllium aluminum composite materials

[0096] Annealing the beryllium / aluminum composite material obtained in step 3;

[0097] The annealing process is as follows: the temperature is 470° C. and the holding time is 1.5 h.

[0098] The density of the beryllium aluminum composite material obtained in Example 3 is 99%, the elastic modulus is 201 GPa, the tensile strength is 650 MPa, and the elongation is 5.5%.

Claims

1. A method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding by matrix alloying, characterized in that: The preparation method of a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying is carried out in the following steps:

1. Weighing of raw materials: Weigh beryllium powder in a sealed glove box; weigh Al-Zn master alloy block, Al-V master alloy block and pure aluminum block at the same time; The ratio of the mass of the beryllium powder to the total mass of the Al-Zn master alloy block, the Al-V master alloy block and the pure aluminum block is 1:10-20; 2. Preparation of Beryllium Powder Preform The beryllium powder weighed in step 1 is placed in a mold, compacted, and then cold pressed to obtain a preform; 3. Preparation of Beryllium Aluminum Composite Materials The Al-Zn master alloy block, the Al-V master alloy block and the pure aluminum block weighed in step 1 are melted to obtain a liquid alloy, the liquid alloy is poured into a mold containing a preform, the mold is preheated and pressure infiltration is performed, and a beryllium / aluminum composite material is obtained after solidification; The mechanical pressure applied during the pressure infiltration is 80-120 MPa, and the pressure holding time is 1-5 min; 4. Heat treatment of beryllium aluminum composite materials The beryllium / aluminum composite material obtained in step three is annealed.

2. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding by matrix alloying according to claim 1, characterized in that: The purity of the beryllium powder in step 1 is 99%.

3. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying according to claim 1, characterized in that: The purity of the pure aluminum block in step 1 is 99.99%.

4. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying according to claim 1, characterized in that: In step 1, the beryllium powder particles in the beryllium powder are spherical or strip-shaped.

5. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying according to claim 1, characterized in that: The cold pressing pressure in step 2 is 50 MPa, and the pressure is maintained for 10 to 15 minutes.

6. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying according to claim 1, characterized in that: The smelting temperature in step 3 is 800-860°C.

7. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding by matrix alloying according to claim 1, characterized in that: The smelting temperature in step 3 is 850°C.

8. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying according to claim 1, characterized in that: The temperature of the mold preheating in step 3 is 250°C to 350°C.

9. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding by matrix alloying according to claim 1, characterized in that: The mold preheating temperature in step 3 is 300°C.

10. The method for preparing a lightweight, high-strength and tough beryllium aluminum composite material with strong interface bonding obtained by matrix alloying according to claim 1, characterized in that: The annealing process in step 4 is as follows: the temperature is 420° C. to 520° C., and the insulation time is 0.5 h to 2 h.